2012
DOI: 10.1029/2012gl053476
|View full text |Cite
|
Sign up to set email alerts
|

Linking fluvial bed sediment transport across scales

Abstract: [1] We present a new random walk model for bed load sediment transport that explains the scale-dependency generally observed in transport rates and captures the transient anomalous dispersion often seen in rivers. Particles alternate between mobile and resting phases, with a tempered stable probability distribution for both particle step length and resting time. Tempered fractional mobile-immobile differential equations model the ensemble average of particle dynamics. The model is tested against data from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 20 publications
4
94
0
1
Order By: Relevance
“…The previous discussion has confirmed that the partial transport process of nonuniform bedload is time scale dependent (see for example, Nikora et al, 2002;Zhang et al, 2012). Moreover, the spatial nonlocal feature shown in Fig.…”
Section: Stochastic Model Analysissupporting
confidence: 49%
See 1 more Smart Citation
“…The previous discussion has confirmed that the partial transport process of nonuniform bedload is time scale dependent (see for example, Nikora et al, 2002;Zhang et al, 2012). Moreover, the spatial nonlocal feature shown in Fig.…”
Section: Stochastic Model Analysissupporting
confidence: 49%
“…Furthermore, the transition from super-dispersion to sub-diffusion was observed and modeled by Martin et al (2012). Zhang et al (2012) proposed a tempered random walk model to describe the transition from super-dispersion to sub-dispersion, and the final convergence to Fickian dispersion for bedload sediment transport.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies highlighted that the scaling behavior within a particular scale range as well as the boundaries between the ranges may depend on specific transport conditions or motion modes [5,10,14,18,22]. For instance, the transition from the intermediate scale range to the global range, expressed in terms of tu à =d (t is time, u à is friction velocity, d is particle diameter) has been found to vary from tens [14,17] to hundreds [3,22]. This discrepancy is likely to be a result of using the same dimensionless argument tu à =d for all scale ranges while it may be applicable only at shorter times corresponding to the local and intermediate scale ranges where particle dynamics effects are dominant.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion rate, expressed as the variance of the tracers location, depends on the observation time scale (Nikora et al, 2002;Zhang et al, 2012). At long time, the variance increases linearly with time (Sayre and Hubbell, 1965;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…, indicates anomalous diffusion (Nikora et al, 2002;Zhang et al, 2012). In the meantime, its skewness increases as γ ∝ t 4 .…”
mentioning
confidence: 99%